Analisis Peran Audit Internal dalam Meningkatkan Efektivitas Pengendalian Arus Kas Perusahaan - Mawaddah Mawaddah; Marwah Marwah; Masyhuri Masyhuri (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the contribution of internal audit in enhancing the effectiveness of cash flow control through a systematic review of publicly available literature, including official publications from OJK, BI, BPS, and academic journals. Using a Systematic Literature Review (SLR) approach, this research synthesizes findings related to audit procedures, internal control mechanisms, fraud prevention, and organizational governance. The results indicate that internal audit plays a crucial role in strengthening the structure of internal control, improving the accuracy of cash transaction records, and ensuring compliance with authorization and verification procedures. Internal audit also contributes to identifying early indicators of misstatements, irregularities, and fraud risks within the cash flow cycle. Moreover, the competence, independence, and professionalism of internal auditors significantly influence the quality of audit outcomes and the reliability of financial information produced. This study concludes that internal audit is a strategic function that not only safeguards company assets but also enhances financial transparency, accountability, and decision-making effectiveness. The implications highlight the need for continuous auditor development and the adoption of robust internal control frameworks to optimize cash flow governance.